Recent trends in food processing : the global scenario - Thyagarajan, D., editor; Ashok, A., editor; Ramasamy, D., editor; Surendraraj, A., editor; Sujatha, G., editor (New Delhi : SSPH, 2014)
Includes bibliographical references